A EVOLUÇÃO DO DIREITO À EDUCAÇAO NO BRASIL REPUBLICANO - Marinelli, Célia Regina Gonçalves (2006)
This investigative work had as objective the evolution analysis of the right to education in the constitutional texts of the republican Brazil. The path of constitutional juridical mediation was chosen to permit reveal the relationship among education, society and the State considering the possibility of learning the limitations that it implies to this kind of social practice, as well as, to understand the material conditions that effectively the State instates a way to favorably flow the right to education. The right to education analysis in the constitutional-juridical apparatus towards the sociological focus was done by approaching interests conflicts presented in the moment of constitutional text elaboration, through the theoretical and methodological perspective proposed by Saes (2003), as a reference to the study of the existing connections between social practice and constitutional-educational legislation. This study was then built since the following conceptual axles: education as a social practice inherent to human existence, in a broad sense, and the literate education as a need imposed by the production relations organization in the capitalist society, according to the proposed by Saviani (2004); configured afterwards as a right, understood as a historical and social phenomenon necessary to the functionality or re-production of a determined kind of society, specially concerning the historical creation of an individual form of right, the constitution of the juridical personality, according to Miaille thoughts (1994) and a citizenship construction in the capitalist ordinance, as a result of the authority relation changes between the state and individuals, according to a theoretical pointed by Bendix (1996), considering the extension, achieving, depth and precision of the right to education declaration, taken as study categories, variables presented in constitutions adopted by modern burgesses States explained by the interests conflicts that cross the social life